INVENTORY DATA PROCESSING "GEMA AGENCY" - Herlina Herlina; Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Technological progress also affects services in the business world, every business is required to further improve service quality with more efficient ways of working. one of them is an echo agency that is located in jakarta is a trading company which has as its main activity which is engaged in selling and buying as well as tabloid newspapers every day or every week to provide information to the reader. As agent, must have inventory or tabloid newspapers are the various forms and its unit price. for that needed a good inventory processing. in order to produce accurate information and can be used to control the quality and quantity of supplies. manual inventory management as it had been run during this very lack of efficient and adequate.